Web-based Interactive 3D Modeling and Visualization of the Human Brain towards Anatomy Education - Gutierrez-Sanchez, Ma. de Jesus; Gonzalez-Islas, Juan-Carlos; Franco-Arcega, Anilu; Suarez-Navarrete, Alberto; Robles-Guzman, Jose Gregorio; Torres-Samperio, Gonzalo Alberto (Revista Mexicana de Ingenieria Biomedica, 2024)
Today, visualization of 3D medical images is an essential tool for medical education. Web-based 3D tools for the teaching-learning process have turned out to be an efficient alternative to conventional systems. In this work, we aim the modeling process and 3D web-based interactive visualization of the human brain using 3D web technologies and an improvement of the Methodology for the Development of Virtual Reality Educational Environments (MEDEERV, for its acronym in Spanish). 20 undergraduate medicine, dentistry, gerontology, and computer science students performed a brain model usability test (9 women; 11 men, mean age = 22.1 years, SD = 0.70). To this end, we used a post-test questionnaire with Likert scale answers whose alpha of Cronbach was 0.93. The proof of concept of the brain model that we have developed in this work provides evidence of the viability of the system to be used as a web tool for basic neuroanatomy learning. The main contribution of this work focuses on the implementation of MEDEERV to model the 3D human brain, plus the usability testing for reengineering feedback. This approach to modeling, visualizing, and evaluating could be used in other areas of human anatomical teaching. Although the experimental results show a good user experience, functionality and usability, it is necessary to generate a new version and carry out a study with a larger and more specific population with knowledge of brain anatomy.